Optimizing Postoperative Pain Management After Endoscopic Sinus Surgery in Indonesia: A Comparative Study of Analgesic Regimens - Nabila Saraswati; Made Swastika; Zahra Amir; Husin Sastranagara; Bernadette Wilson (Sriwijaya Journal of Otorhinolaryngology, 2023)
Introduction: Endoscopic sinus surgery (ESS) is a frequently performed procedure for chronic rhinosinusitis in Indonesia. Effective postoperative pain management is vital for patient comfort, early recovery, and minimizing healthcare expenses. This study compared the efficacy of different analgesic regimens in managing postoperative pain after ESS in an Indonesian population. Methods: This prospective, randomized controlled trial involved 120 patients undergoing ESS at a tertiary hospital in Indonesia. Patients were randomly allocated to one of three groups: Group A received intravenous patient-controlled analgesia (PCA) with morphine, Group B received a combination of intravenous ketorolac and oral paracetamol, and Group C received oral paracetamol alone. Pain intensity was evaluated using the Visual Analog Scale (VAS) at 2, 6, 12, and 24 hours postoperatively. The requirement for rescue analgesia and the occurrence of adverse effects were also documented. Results: Group A (PCA with morphine) exhibited significantly lower VAS scores at all time points compared to Group B (ketorolac and paracetamol) and Group C (paracetamol alone) (p<0.001). Group B showed lower VAS scores than Group C at 2 and 6 hours postoperatively (p<0.05). The need for rescue analgesia was significantly higher in Group C compared to the other groups (p<0.001). The incidence of nausea and vomiting was higher in Group A, while constipation was more frequent in Group B. Conclusion: Intravenous PCA with morphine provided superior postoperative pain control after ESS compared to other analgesic regimens. However, the increased incidence of nausea and vomiting should be taken into account. A combination of intravenous ketorolac and oral paracetamol presented a suitable alternative with a more favorable side effect profile. Further investigation is necessary to optimize pain management protocols for ESS in the Indonesian population.